Mitstreiter im Volkstumskampf. Deutsche Justiz in den eingegliederten Ostgebieten 1939-1945 - Becker, Maximilian (De Gruyter, 2014)
In Poland during the Second World War, the German judicial system was part of the National Socialist occupation machine from the outset and became a key element in the policy of Germanization, Germany`s principal objective for the annexed portions of Poland. The courts systematically discriminated against Poles, and between September 1939 and the beginning of 1945, imposed thousands of death sentences.
German
Keywords: National Socialism; legal history history of justice; German occupation of Poland